Association of rs9939609 FTO Gene Polymorphism as a Risk Factor of Obesity in Adults - Pratamawati, Tiar Masykuroh; Sadji, Angel Angriani Elma Budai; Brajadenta, Gara Samara; Nauphar, Donny (GHMJ (Global Health Management Journal), 2024)
Background: The cause of obesity is an imbalance between the number of calories taken and the amount burned. Obesity is a complex disease. The FTO rs9939609 gene polymorphism is one of the genetic factors that contribute to obesity in addition to environmental factors. Numerous researches have suggested a connection between the prevalence of obesity and the FTO rs9939609 gene polymorphism Aims: The purpose of this study is to ascertain how the FTO rs9939609 gene polymorphism relates to the prevalence of adult obesity. Methods: At the Biomolecular and Genetics Laboratory of the UGJ Faculty of Medicine, an analytical observational study using a case-control design was carried out with 84 participants, 42 subjects in case group, and 42 subjects in control groups. Data were collected utilizing DNA from blood collection, PCR-RFLP for genotyping, and 2.5% electrophoretic gel for visualization. Chi-square was used for data analysis. Results: Findings showed that there is no link between the FTO rs9939609 polymorphism and the prevalence of obesity (p>0.05, OR=0.710). Conclusion: In the Indonesian population, the FTO rs9939609 gene polymorphism is not associated with an increased risk of obesity.